Functional outcome after surgery in patients with bone sarcoma around the knee; results from a long‐term prospective study. Issue 8 (6th April 2017) - van Egmond‐van Dam, Janneke C.; Bekkering, W. Peter; Bramer, Jos A.M.; Beishuizen, Auke; Fiocco, Marta; Dijkstra, P.D. Sander
Abstract : Background and Objectives: In a previous conducted study functional outcome of young patients with bone sarcoma located around the knee was longitudinally evaluated during the first 2 years postoperatively. Functional outcome improved significantly over the first 2 years. The purpose of this descriptive study was to evaluate the functional outcome of these patients at long‐term follow‐up of 7 years. Methods: Functional outcome was assessed with the TESS, MSTS, Baecke questionnaire, and three functional performance tests: time up and down stairs (TUDS), various walking activities (VWA), and the 6‐min walking test (6MWT). Linear Mixed Model has been employed for the repeated measurements. Results: Twenty patients of the original study ( n  = 44) participated in the current study. Fifteen limb‐salvage and five ablative surgery patients, median follow‐up 7.4 years (6.8‐8.0) (CI 95%), mean age 22.3 years (18.2‐31.6). Between 2 and 7 years after surgery, 8 limb‐salvage patients (53%) encountered surgery related complications. Questionnaires and functional performance tests showed no significant difference in functional outcome between 2 years and 7 years after surgery ( P  < 0.05). Conclusions: Between 2 years and follow‐up at average 7 years after surgery no further improvements were noticed at young patients with a bone sarcoma located around the knee.